Land use change has profoundly altered the process of bacterial community assembly in the northeastern black soil zone - Sun, Ning; Zhao, Xu; Liu, Fangyuan; Song, Ge; Zhang, Mengmeng; Song, Fuqiang (Frontiers in Microbiology, 2025)
IntroductionSoil microorganisms play a critical role in maintaining ecological functions; however, their responses to grassland reclamation and tillage remain poorly understood. This study aims to investigate the effects of these practices on soil bacterial communities in the Northeast China Black Soil Region.MethodsWe utilized high-throughput sequencing to compare soil bacterial community characteristics between undisturbed grasslands (CK) and reclaimed croplands (F). The analysis focused on assessing structural changes and shifts in ecological strategies of soil bacterial communities under both land-use types.ResultsOur findings revealed that croplands exhibited higher soil pH and elevated concentrations of nutrients such as ammonium nitrogen, nitrate nitrogen, and total phosphorus compared to pristine grasslands. The Average Variation Degree (AVD) indicated that bacterial communities in cropland soils had greater compositional stability. Additionally, dominant bacterial genera, particularly Sphingomonas and Pseudarthrobacter, were more prevalent in croplands. Using random forest classification modeling, we identified several rare bacterial genera, including Rhodomicrobium, Amycolatopsis, and Clostridium, which, despite each representing less than 1% of the community, played critical roles in shaping microbial community structure. Co-occurrence network analysis showed that reclamation reduced interspecies interactions and significantly decreased network complexity, connectivity, and cohesion (P < 0.05). Neutral community assembly modeling further indicated that stochastic processes were more dominant in the assembly of bacterial communities in croplands compared to undisturbed grasslands.DiscussionThis study provides a comprehensive understanding of how grassland reclamation and tillage influence soil bacterial communities in the Songnen Plain black soil region. The findings enhance our ecological understanding of land use changes and offer valuable insights for the sustainable management of black soil resources and ecosystems.